Development of nanostructured polymeric systems based on ring-opening polymerization (ROP) and reversible addition-fragmentation chain-transfer (RAFT) polymerization - Melchiors, Marina de Souza (2021)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2021.